Risk Factor Analysis Of Nurse’s Depression Level Using The Beck Depression Inventory Method In The Isolation Room For Covid-19 Patients Royal Prima Medan In 2022 - vivian Leoditta Sitinjak; Ermi Girsang; Ali Napiah Nasution (CV. Inara, 2022)
This Corona Virus has been named SARS-CoV 2 and this virus moves from human to human through direct contact and has symptoms ranging from mild to severe. Nurses can experience psychological disorders in the form of depression because they are directly involved in treating Covid-19 patients. The purpose of this study was to analyze risk factors (working time, risk of exposure, workload, stigma, and social support) on the level of depression of nurses using the Beck Depression Inventory method in the isolation room for Covid-19 patients at Royal Prima Hospital Medan in 2022. The type of research used is an analytical study with a cross-sectional approach with primary and secondary data collection in February - March 2022. The number of research samples is 95 nurses who work in the Covid-19 isolation room. The data were analyzed univariately to see a descriptive picture, bivariate using the product-moment test, and multivariate by using the multiple logistic regression test. The results of this study are; based on age the most in the age group 20-30 years (93.7%), gender, dominated by women (73.7%). Based on education, it was found nurses with a Diploma education (75.8%), work 1-2 years (50.5%). Based on marital status, predominately single (76%). In the bivariate analysis, there was a relationship between risk factors and the level of depression of nurses in the Covid-19 isolation room at Royal Prima Hospital Medan in 2022. In the multivariate analysis, working time (0.007), risk of exposure (0.003), workload (0.002), stigma (0.024) ), and social support (0.012). The conclusion of this study is that there is an influence of risk factors on the level of depression of nurses in the Covid-19 isolation room at Royal Prima Hospital Medan in 2022.